Spore editor hands over the baton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Robert Delleré, the chief editor of Spore since publication began, recently retired from his post at CTA. Field and administrative experience of agricultural development gained earlier in his career in Africa and the Caribbean instilled in Mr...